2015
DOI: 10.1007/978-3-319-27261-0_42
|View full text |Cite
|
Sign up to set email alerts
|

On the Readability of Boundary Labeling

Abstract: Boundary labeling deals with annotating features in images such that labels are placed outside of the image and are connected by curves (so-called leaders) to the corresponding features. While boundary labeling has been extensively investigated from an algorithmic perspective, the research on its readability has been neglected. In this paper we present the first formal user study on the readability of boundary labeling. We consider the four most studied leader types with respect to their performance, i.e., whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…For the inner-placement, leader lines are usually very short since insets are positioned as close as possible to their source annotation. Barth et al [2] have shown that straight leader lines for boundary labeling, which is similar to our outer-placement (subsection 4.2), perform comparably to or even better than more sophisticated methods.…”
Section: Inset and Leader Line Designsupporting
confidence: 70%
“…For the inner-placement, leader lines are usually very short since insets are positioned as close as possible to their source annotation. Barth et al [2] have shown that straight leader lines for boundary labeling, which is similar to our outer-placement (subsection 4.2), perform comparably to or even better than more sophisticated methods.…”
Section: Inset and Leader Line Designsupporting
confidence: 70%
“…However, edges can only be drawn as chains of horizontal and vertical segments (which may partially overlap), and the labels are placed outside a single rectangular region that encloses all vertices. Variants of the boundary labeling problem, where each fixed vertex is associated with exactly one label are also studied in the literature (see, e.g., [2,4,23]). Note that, in labeling problems, labels are geometric shapes of non-empty area, while we model mobile vertices as points.…”
Section: Point Labelingmentioning
confidence: 99%
“…our experiments we have chosen the shells such that less than 0.9% of the labels in handmade drawings violate this property; see also Section 7. We further speed up Step 2 (2). To that end let I C [ 1 , 2 ] be the currently considered capstone instance and let s 1 and s 2 be the sites of 1 and 2 , respectively.…”
Section: Contour and Shellsmentioning
confidence: 99%
“…Consider a capstone instance I C [ 1 , 2 ] such that both labels 1 and 2 are right labels. Let D be the descendants computed in Step 2 (2). Indeed we only need to consider the descendants in D with the leftmost site s among all those descendants.…”
Section: Miscellaneousmentioning
confidence: 99%
See 1 more Smart Citation